Association of body fat composition and obstructive sleep apnea in the elderly: A longitudinal study. (7th June 2015) - Saint Martin, Magali; Roche, Frédéric; Thomas, Thierry; Collet, Philippe; Barthélémy, Jean Claude; Sforza, Emilia
<x xml:space="preserve">Abstract</x> Objective Obesity and aging are considered risk factors for developing sleep apnea syndrome (OSA). The aim of this study was to determine the association between body fat composition and OSA in healthy elderly subjects examined in a 7‐year longitudinal study. Methods A total of 209 elderly with unrecognized OSA aged 68.3 ± 0.8 years underwent a clinical, ambulatory nocturnal respiratory recording, and anthropometric as well as body fat composition assessment by dual‐energy X‐ray absorptiometry (DEXA) at baseline and follow‐up. Results At study entry, 50.3% of the population showed an apnea+hypopnea index (AHI) <15 with a mean AHI of 16.8 ± 11. At follow‐up, a reduction of OSA cases (42%) was evident with a mean AHI of 14.6 ± 10.2. The DEXA data demonstrated that body mass and total lean mass were reduced at follow‐up, while central and peripheral fat mass showed a slight increase. Correlation analysis between the changes in DEXA measurements versus the changes in AHI and the indices of nocturnal hypoxemia showed an absence of a statistical correlation. Conclusions The lack of correlation between the DEXA measurement changes and the changes in the AHI confirm our previous data on the absence of a central fat mass effect on OSA in the elderly.